ECOLOGICAL ASPECTS OF MONOGENEAN GILL PARASITES (PLATYHELMINTHES) FROM HOPLIAS AFF. MALABARICUS (BLOCH, 1794) (PISCES, ERYTHRINIDAE) IN A NEOTROPICAL FLOODPLAIN - Junio da Graça, Rodrigo (2013)
We analyzed 54 specimens of Hoplias aff. malabaricus (Bloch, 1794) collected between March 2010 and March 2011 from the upper Paraná river Neotropical floodplain, Brazil. All hosts were parasitized by at least one species of Monogenea. The parasites species with higher prevalence were Urocleidoides cuiabai Rosim, Mendoza-Franco & Luque, 2011 (96.29 %) and U. malabaricusi Rosim, Mendoza-Franco & Luque, 2011 (92.59%). The community of gill ectoparasites examined showed an aggregated pattern. Urocleidoides cuiabai was the dominant species in the sample (C > 0.25). The parasitic abundance showed significant positive correlation with the standard length of the host for U. malabaricusi and U. eremitus Kritsky, Thatcher & Boeger, 1986. There were significant differences in the abundance values between male and female fish to the species of parasites Urocleidoides brasiliensis Rosim, Mendoza-Franco & Luque, 2011 and U. cuiabai. The gonad maturation stages of the host did not influence the levels of parasitism. Four species of parasites showed positive and significant correlation with parasitic abundance and the relative condition factor. The Ivinheima river presented higher abundance of parasitism in relation to other subsystems. The ecological study of monogeneans can provide a greater knowledge of the biology of these parasites and their hosts, the collection site, and even how the host responds to the presence of these parasites. We discuss the factors that were fundamental in the levels of parasitism in this important fish species in the floodplain of the upper Paraná river.